“Mendengar dan Melakukan Perintah Tuhan Mendatangkan Berkat” Kajian Hermeneutik Kritik Historis Terhadap Ulangan 28: 1-14 - Mandagi, Pingkan Gratcia; Lumintang, Ferry S. N. (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
Blessings are gifts that God gives in human life. There are those who want to feel and enjoy God's blessings, but the life they live does not reflect obedience to God. Even when they receive blessings, they forget themselves and forget to thank God for the blessings they enjoy. In Deuteronomy 28:1-14, when the Israelites were about to enter the land of Canaan and live in the promised land that the LORD God had given them, Moses gave a speech in which he spoke about reminding the Israelites to be faithful to hear God's commands and to obey Him. The promise when they were willing to obey and be faithful to Him was the abundant blessings that God would give them but if they violated then there were curses that would befall them. This scientific work uses the Hermeneutic method of historical criticism in order to obtain the right meaning and theology regarding obedience to God, is the main key for believers to obtain blessings that come from God.